Student’s view toward utilizing Quizizz application to increase English learning motivation - Dhisa, Hadisty Rahma; Melvina, Melvina; Afriyanti, Rika (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This study aims to analyze students' views on the use of the Quizizz application to improve students' English learning motivation at SMA 15 Padang. With the development of technology, innovative learning methods are important to improve students' learning motivation. This study uses a descriptive qualitative approach method, where data is collected through questionnaires distributed to 31 students and 5 students to be interviewed. Then the data from the Questionnaire is analyzed through Descriptive Statistics, and the results of the interviews are analyzed using Thematic Analysis. The results showed that 78% of students felt positive about using Quizizz; students felt that it not only made the learning process more enjoyable, but also increased interaction between students and teachers. So that students become motivated in learning English, so that the English skills possessed by students increase. Keywords: Quizizz; student’s view; motivation;